Oxidative Stress as a Mechanism of Added Sugar-Induced Cardiovascular Disease - Prasad, Kailash; Dhar, Indu (International Journal of Angiology, 2014)
Added sugars comprising of table sugar, brown sugar, corn syrup, maple syrup, honey, molasses, and other sweeteners in the prepared processed foods and beverages have been implicated in the pathophysiology of cardiovascular diseases. This article deals with the reactive oxygen species (ROS) as a mechanism of sugar-induced cardiovascular diseases. There is an association between the consumption of high levels of serum glucose with cardiovascular diseases. Various sources of sugar-induced generation of ROS, including mitochondria, nicotinamide adenine dinucleotide phosphate-oxidase, advanced glycation end products, insulin, and uric acid have been discussed. The mechanism by which ROS induce the development of atherosclerosis, hypertension, peripheral vascular disease, coronary artery disease, cardiomyopathy, heart failure, and cardiac arrhythmias have been discussed in detail. In conclusion, the data suggest that added sugars induce atherosclerosis, hypertension, peripheral vascular disease, coronary artery disease, cardiomyopathy, heart failure, and cardiac arrhythmias and that these effects of added sugars are mediated through ROS.
Keywords: added sugars; reactive oxygen species; atherosclerosis; hypertension; coronary artery disease; peripheral vascular disease